2020
DOI: 10.1017/s1466252320000043
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability and comparability of prevalence estimates in the wild bird literature: methodological and epidemiological considerations

Abstract: Wild birds have been the focus of a great deal of research investigating the epidemiology of zoonotic bacteria and antimicrobial resistance in the environment. While enteric pathogens (e.g. Campylobacter, Salmonella, and E. coli O157:H7) and antimicrobial resistant bacteria of public health importance have been isolated from a wide variety of wild bird species, there is a considerable variation in the measured prevalence of a given microorganism from different studies. This variation may often reflect differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Numerous findings suggest that wild birds, given their ability to fly long distances and their ubiquity, play an important role in the epidemiology and evolution of Campylobacter spp. [8,9]. In addition, some wild bird species have successfully adapted to anthropogenic environments and routinely come into close contact with livestock, domestic animals, and people [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous findings suggest that wild birds, given their ability to fly long distances and their ubiquity, play an important role in the epidemiology and evolution of Campylobacter spp. [8,9]. In addition, some wild bird species have successfully adapted to anthropogenic environments and routinely come into close contact with livestock, domestic animals, and people [9].…”
Section: Introductionmentioning
confidence: 99%
“…[8,9]. In addition, some wild bird species have successfully adapted to anthropogenic environments and routinely come into close contact with livestock, domestic animals, and people [9]. They are, therefore, considered as reservoirs of farm animals and human infection [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…(2016a) suggested that raccoons likely acquired resistant bacteria from dumpsters within conservation areas. Another limitation of this work relates to our method of sampling raccoons; since this was conducted with baited traps, the selection of study individuals is likely biased to some degree (Vogt et al., 2020). As a result of sampling animals in this way, it is possible that our study group represents a subpopulation of raccoons that may be either more or less likely to carry Campylobacter due to differences in physiology, behaviour, and/or feeding habits.…”
Section: Discussionmentioning
confidence: 99%
“…only 10 locations). Such details were qualitatively iden- traps, the selection of study individuals is likely biased to some degree (Vogt et al, 2020). As a result of sampling animals in this way, it is possible that our study group represents a subpopulation of raccoons that may be either more or less likely to carry Campylobacter due to differences in physiology, behaviour, and/or feeding habits.…”
Section: Sub-categorymentioning
confidence: 99%
“…Seagulls, birds, land mammals, cetaceans, and other wildlife may also be contributors of AMR bacteria and ARGs in the environment [190][191][192][193][194][195][196]. However, the human health risks associated with AMR bacteria and ARGs in wildlife have not been fully evaluated, given the lack of surveillance data for clinically relevant AMR bacteria and ARGs in wildlife [193].…”
Section: Birds and Other Wildlifementioning
confidence: 99%